2009
DOI: 10.1016/j.contraception.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

How does gestational diabetes affect postpartum contraception in nondiabetic primiparous women?

Abstract: Background: The aim of the study is to explore the effect of gestational diabetes mellitus (GDM) on postpartum contraception among nondiabetic primiparous women. Study Design: Secondary analyses of 2004–2005 Pregnancy Risk Assessment Monitoring System data from Michigan and Oregon. Methods: Analyses were performed on 2332 women, taking complex survey design into consideration. Crude and adjusted odds ratios (cOR; aOR) and their 95% confidence intervals (CI) were obtained using logistic regression analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Those who have completed child-bearing and do not desire pregnancy, surgical sterilization would be preferred. [42][43][44] The above timeline ensures that Indian women will be evaluated at least a couple of times at various life stages, for early identification and management of diabetes.…”
Section: Post-partum Phase: All Postpartum Women With Gdm During Pregnancymentioning
confidence: 99%
“…Those who have completed child-bearing and do not desire pregnancy, surgical sterilization would be preferred. [42][43][44] The above timeline ensures that Indian women will be evaluated at least a couple of times at various life stages, for early identification and management of diabetes.…”
Section: Post-partum Phase: All Postpartum Women With Gdm During Pregnancymentioning
confidence: 99%
“…Women’s preferences for the different types of contraceptives and their contraceptive uptake have shifted in recent years. Older studies found that women with a history of GDM were more likely to choose tubal sterilization and less likely to choose DMPA 93. A more recent study showed that women with a history of GDM were more likely than the general population to use highly-effective, reversible contraception 73.…”
Section: Contraceptive Recommendations and Future Health Implicationsmentioning
confidence: 99%
“…Thus, in a secondary analysis of the 2004–2005 Pregnancy Risk Assessment Monitoring System database conducted in the United States (in Michigan and Oregon) by Beydoun et al, no difference in the percentage of use of hormonal and non-hormonal contraceptives was observed among primiparous women without diabetes and those with a prior history of GDM, although there was a higher frequency of female sterilization and a lower use of depot-MPA among the group of patients reporting GDM diagnosis. 67 The review conducted by Napoli et al in 667 Italian diabetic women (type 1 DM or type 2 DM) found that 30.4% of women used hormonal contraception, 12% used an IUD, 47% used natural or barrier methods, and 10.7% used no method contraception. The percentage of women using oral contraceptives differed between women with type 1 DM and type 2 DM.…”
Section: Prevalence Of Hormonal Contraception Use Among Women With DImentioning
confidence: 99%